Hybridisation of Muslim Millennials’ Religious Identity in the Digital Era - Nurfitria, Nadia (Digital Muslim Review, 2023)
This article explores the social movement paradigm in the millennial Muslim generation in the digital era through social media platforms. This research uses the concept of social movement as one of the collective behaviours, making the millennial generation’s social movement a new phenomenon in the Islamic movement in Indonesia. This research uses the Interpretative Phenomenology Analysis (IPA) approach (Roller, 2015; Smith et al., 2009) to understand, analyse, and explore the phenomenon. The socio-religious movement for the millennial Muslim generation through Islamic studies on social media was examined using a qualitative approach. The research findings reflect that the social movement occurs communally, giving birth to a socio-religious movement. The millennial Muslim movement has built a new identity as a religious community that obeys Islamic rules. The social movement intends to make young people close to the Qu’ran, pray on time, actively seek religious knowledge, and spread the message of Islam through social media platforms.